Five willow varieties cultivated across diverse field environments reveal stem density variation associated with high tension wood abundance - Berthod, Nicolas; Brereton, Nicholas J. B.; Pitre, Frédéric E.; Labrecque, Michel (Frontiers in Plant Science, 2015)
Sustainable and inexpensive production of biomass is necessary to make biofuel production feasible, but represents a challenge. Five short rotation coppice (SRC) willow cultivars, selected for high biomass yield, were cultivated on sites at four diverse regions of Quebec to determine their bioenergy potential in contrasting environments. Wood composition and anatomical traits were characterized. Tree height and stem diameter were measured to evaluate growth performance of the cultivars according to the diverse pedoclimatic conditions. Each cultivar showed very specific responses to its environment. While no significant variation in lignin content was observed between sites, there was variation between cultivars. Surprisingly, the pattern of substantial genotype variability in stem density was maintained across all sites. However, wood anatomy did differ between sites in a cultivar (producing high and low density wood), suggesting a probable response to an abiotic stress. Furthermore, twice as many cellulose-rich G-fibers, comprising over 50 % of secondary xylem, were also found in the high density wood, a finding with potential to bring higher value to the lignocellulosic bioethanol industry